Adequacy of telework spaces in homes during the lockdown in Madrid, according to socioeconomic factors and home features. (December 2021) - Cuerdo-Vilches, Teresa; Navas-Martín, Miguel Ángel; March, Sebastià; Oteiza, Ignacio
Highlights: This study examines the influence of socioeconomic factors and household features on the adaptation of telework spaces for Madrid (Spain), during the confinement decreed at the beginning of the COVID-19 pandemic. The socio-economic profile of teleworkers indicated a high level of studies, mostly salaried workers, a high level of average income, and therefore a privileged condition. A third of the households considered their telework spaces as inadequate, being related to: the lack of exclusive spaces to work; be more than one teleworker per household; having poor digital resources; or to the inadequacy of the characteristics of such spaces. Although this study contributes to evaluating households' perception of the adequacy of homes for teleworking in an unusual context, it may be helpful for future analysis of teleworking and those aspects in households that influence such perception. Abstract: In Spain, the COVID-19 confinement was carried out in the spring of 2020. All non-essential activities were temporarily suspended. This brought with it the adaptation to home office (telework), still emerging in Europe, and more in Spain. Although the response in general has been positive, the conditions to which families have been subjected to telework cannot be considered normal. In this context, an online survey was requested to find out the experience of confined households in relation to the dwelling adaptation and satisfaction following the new needs in lockdown. The data obtained on workspace perception and its adequacy were studied in Madrid, stratified by gender and average income, for a sample of 256 households with people teleworking or studying. The results showed that the adequacy of telework spaces were insufficient for a third of the households, with no significant relationship with most of socioeconomic variables, nor with home characteristics. The variables related to this inadequacy of the spaces were: the number of people who work or study at home; the lack of exclusive spaces for teleworking; and the availability of digital resources. This perception also depended on the qualities of the teleworking space, as size, furniture and lighting, among others.